Knowledge and Conversation: Linguistic Vices in the Context of Grice’s Theory of Implicatures - Šetar, Niko (Analiza: časopis za kritično misel, 2025)
Recently, informal epistemology has centred on a theory of epistemic virtues and vices, rooted in Aristotle's virtue ethics and divided into two key approaches: reliabilism and responsibilism, which offer related but contrasting views. Quassim Cassam's work has advanced the perception of vices as behaviours that prevent access to knowledge, classified by fidelity. The theory of epistemic virtues and vices has also led to the theory of argumentative virtues, notably developed by Andrew Aberdein, who examines the transmission of knowledge and belief through argumentation. Argumentative vices, by the same theory, are characteristics that lead to fallacious argumentation and acceptance of flawed arguments. However, Cohen argues that not all knowledge transfer – such as inferential statements or classroom conversation – is necessarily argumentative. Since belief transfer can occur non-argumentatively, it is reasonable to seek an argumentation-related vice in such cases. Grice's theory of implicatures suggests flawed statements generate pragmatic implications, creating space to examine epistemic vices in language within non-argumentative belief transfer contexts.
Keywords: epistemic vice; argumentative vice; conversation; implicature; epistemology; philosophy of language